Analisis Kasus Pembobolan Dana Nasabah Citibank Dan Penerapan Strategi Anti Fraud Dari Otoritas Jasa Keuangan - Aradhea, Ariya Mega; Fadlian, Aryo (Jurnal Ilmiah Wahana Pendidikan, 2024)
The study contained in this research contains a criminal act of embezzlement and money laundering in the Citibank case. Citybank received reports from several customers regarding the disappearance of the customer's funds in their savings. Then Citibank reported the incident to the police. After the investigation was carried out, it turned out that there was a breach of customer funds by a senior city bank employee named Malinda Dee alias Inong Malinda. In this journal, several issues that will be published include; Analysis of cases of embezzlement of money and banking crimes, and ways in which the authorities' policies prevent banking fraud. The banking business is a business that requires high levels of supervision and honesty. Customer funds that have been deposited in the bank must receive close supervision. According to the legal viewpoint, the prevention of the above events can be minimized by POJK No. 39 Year 2019 about anti-fraud strategy.